2014
DOI: 10.1107/s1600536814009027
|View full text |Cite
|
Sign up to set email alerts
|

Bis(4-hydroxy-3-methoxybenzaldehyde 4-phenylthiosemicarbazonato-N1,S)nickel(II)

Abstract: In the title compound, [Ni(C15H14N3O2S)2], the NiII atom lies on a center of symmetry. The deprotonated ligands act as N,S-donors, forming five-membered metalla-rings. The NiII atom is four-coordinated in a slightly distorted square-planar environment. In the crystal, the discrete complex mol­ecules are linked by weak N—H⋯O hydrogen bonds, generating chains along [110]. The chains are further connected via weak O—H⋯N inter­actions into a layered network extending parallel to (001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
4
2
0
Order By: Relevance
“…These observed values of contact distances and bond angles fall in the range for anagostic interactions reported by Brookhart et al (2007). Similar observations have been reported recently by de Oliveira et al (2014).…”
Section: Figuresupporting
confidence: 93%
See 2 more Smart Citations
“…These observed values of contact distances and bond angles fall in the range for anagostic interactions reported by Brookhart et al (2007). Similar observations have been reported recently by de Oliveira et al (2014).…”
Section: Figuresupporting
confidence: 93%
“…This is in close agreement with previously reported data (Sampath et al, 2013, Suganthy et al, 2013. A remarkable tetrahedrally distorted square-planar coordination geometry is shown by the nickel metal ion, with the two ligands displaying a less common cis N,S-chelation mode (de Oliveira et al, 2014). The Ni-S and Ni-N bond lengths (Table 1) and the N1-Ni1-S2 and N4-Ni1-S1 bond angle of 159.86 7and 159.67 7, respectively, confirm the distortion from a typical coordination geometry.…”
Section: Structural Commentarysupporting
confidence: 92%
See 1 more Smart Citation
“…For an agostic interaction, that involves a covalent or a three-center, twoelectron bond, an HÁ Á Ámetal distance of at least 2.3 Å is required. The C7-H7Á Á ÁNi1 and C19-H19Á Á ÁNi1 angles are 120.1 and 119.7 , being in agreement with literature data for another nickel complex with anagostic interactions (de Oliveira et al, 2014b).…”
Section: Figuresupporting
confidence: 90%
“…The hydrazinic H atom can be easily removed and the negative charge is then delocalized over the C-N-N-C-S backbone, which enables chemical bonding with many different metal ions (Lobana et al, 2009). However, a cis configuration of the ligated molecules is a rather uncommon coordination mode for mono-thiosemicarbazones and, as far as we know, there is only one Ni II mono-thiosemicarbazone complex reported in ISSN 2056-9890 the literature, with N-phenyl-2-(1,2,3,4-tetrahydronaphthalen-1-ylidene)hydrazinecarbothiamide as ligand (for the ligand crystal structure, see: de Oliveira et al, 2014a; for the crystal structure of the complex, see: de Oliveira et al, 2014b). It can be suggested that the molecular symmetry decreases from a trans to a cis configuration, possibly by loss of inversion symmetry at the central metal cation, which is compensated for by HÁ Á ÁNi intramolecular interactions and hydrogen-bond formation with solvent molecules.…”
Section: Chemical Contextmentioning
confidence: 99%